Empowering Employee Engagement: The Mediating Role Of Job Satisfaction In The Influence Of Islamic Work Values - Nitami Galih Pangesti; Candraningrat Candraningrat (Journal of Halal Research, Policy, and Industry, 2025)
This study examines the positive influence of Islamic Work Values (IWV) on employee job satisfaction and engagement, with job satisfaction acting as a mediator in this relationship. Islamic Work Values, rooted in Islamic ethical and moral teachings, encourage behaviours such as integrity, fairness, and accountability, which promote positive interactions and a supportive work environment. This study is a quantitative study with a sample size of 100 employees. The results of this study explain that there is an influence between Islamic work values and employee engagement and job satisfaction as a mediator.